Respuestas

2012-04-23T00:07:47+02:00

2x+3y=6    /*3

3x+2y=14  /*2

 

   6x+9y=18

 - 6x+4y=28

 

        5y=-10

          y=-10/5

          y=-2

 

2x+3*-2=6

2x-6=6

2x=6+6

2x=12

x=12/6

x=2

¡La mejor respuesta!
2012-04-23T00:17:25+02:00

-3(2x+3y)=-3(6)

2(3x+2y)=2(14)

________________

-6x-9y=-18

 6x+4y=28

___________

-5y=10

   y=-2

________

Reemplazas y=-2 en cualquier ecuacion:

2x+3(-2)=6

      2x-6=6

         2x=6+6

           x=12/2

           x=6

 

Respuesta: y=-2 x=6 ... Espero que sea lo que estabas buscando =)